2010
DOI: 10.3382/ps.2009-00494
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-aided protein extraction of chicken dark meat: Composition and stability to lipid oxidation of the recovered proteins

Abstract: Chicken dark meat has been considered as a major underused commodity due to the increasing demand for further-processed breast meat products. One option to increase the utilization of chicken dark meat is to extract myofibrillar proteins and separate them from fat and pigments to enhance their application for the preparation of further-processed meat products. The objective of the current study was to determine the effect of pH, in the range of 10.5 to 12.0, on the alkaline solubilization process of chicken da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…This trend was also observed after 5 weeks. Lightness is main factor that affects whiteness, and both show positive correlation . The highest chroma value was in the sausage with CCP for the entire 5 weeks ( P < 0.05).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This trend was also observed after 5 weeks. Lightness is main factor that affects whiteness, and both show positive correlation . The highest chroma value was in the sausage with CCP for the entire 5 weeks ( P < 0.05).…”
Section: Resultsmentioning
confidence: 91%
“…Lightness is main factor that affects whiteness, and both show positive correlation. 21 The highest chroma value was in the sausage with CCP for the entire 5 weeks (P < 0.05). According to the study by Min and Green, 22 it was concluded that the highest chroma value of catfish patty is due to the highest yellowness, and similar results were found in this study.…”
Section: Sausage Colourmentioning
confidence: 92%
“…Hue angle values of SPI, 1.5% PPI, and control‐1 were not significantly different; but were significantly higher than 2% PPI and control‐2 samples. Dominance of hue angle value indicates that the color is slightly toward the yellowish spectrum (Hoffman and Mellet 2003), or in other words, reduction in visually perceived redness (Moayedi and others 2010).…”
Section: Resultsmentioning
confidence: 99%
“…This technology efficiently recovers functional and nutritious protein isolates from muscle foods including fish, poultry and their byproducts (Matak et al 2015;Moayedi et al 2010;Omana et al 2010;Hrynets et al 2011;Tahergorabi et al 2011) and has been used to eliminate toxic compounds and off-odour substances contaminated in fish (Marmon et al 2009;Yanpakdee et al 2012). The extraction mechanism of the two processes is to solubilise the muscle proteins at low and high pH to separate soluble proteins, bone, skin, connective tissue, cellular membranes and neutral storage lipids through centrifugation.…”
Section: Introductionmentioning
confidence: 99%